Design, Modeling, Fabrication, and Verification of New Multifunctional MEMS/NEMS Components. Issue 19 (23rd July 2019) - Freitag, Markus; Sauppe, Matthias; Auerswald, Christian; Kriebel, David; Schmidt, Henry; Voigt, Sebastian; Arnold, Benjamin; Markert, Erik; Hahn, Susann; Hiller, Karla; Heinkel, Ulrich; Mehner, Jan
Abstract : The development of a new sensor generation with a significant performance gain is mainly aimed at increasing the sensitivity. In addition to that, a variety of properties such as integrability, power consumption, robustness, reliability, cross‐talk sensitivity, and others, can be equally important. Some properties scale directly with sensitivity, whereas others show trade‐off characteristics. An overview of different approaches for new sensor generations with enhanced performance is presented and discussed in this article. The main focus is on new microelectromechanical systems (MEMS) elements, fabricated within a standard high‐aspect‐ratio micromachining process and capacitive working principle. Herein, a novel MEMS‐based bandpass, a gap reduction technique, fluted electrodes for reduced damping, and a novel direct current/direct current (DC/DC) converter, is proposed. Acoustic emission sensing is chosen as example application to underline the challenging requirements for the design. Furthermore, the recent improvements in technology are presented. Based on bonding and deep reactive ion etching (BDRIE), it allows larger aspect ratios as well as through‐silicon vias and low‐pressure encapsulation. Consistent further miniaturization leads to the use of nanoscopic elements within MEMS as sensing component instead of the conventional electrostatic working principle. Unique properties of graphene rolls or carbon nanotubes (CNTs) enable promising sensitivity improvements if they are integrated at wafer‐level. Therefore, a design concept and formal verification‐tool is presented. Abstract : An overview of different approaches for new electrostatic sensor generations with enhanced performance is presented and discussed in this article. A novel microelectromechanical systems (MEMS) bandpass, a gap reduction technique, fluted electrodes for reduced damping, and a novel DC/DC converter, are presented. For the use of nanoscopic elements within MEMS as sensing component, a formal verification tool is presented.